The Stealth Erosion of Dollar Dominance : Active Diversifiers and the Rise of Nontraditional Reserve Currencies - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2022)
We document a decline in the dollar share of international reserves since the turn of the century. This decline reflects active portfolio diversification by central bank reserve managers; it is not a byproduct of changes in exchange rates and interest rates, of reserve accumulation by a small handful of central banks with large and distinctive balance sheets, or of changes in coverage of surveys of reserve composition. Strikingly, the decline in the dollar's share has not been accompanied by an increase in the shares of the pound sterling, yen and euro, other long-standing reserve currencies and units that, along with the dollar, have historically comprised the IMF's Special Drawing Rights. Rather, the shift out of dollars has been in two directions: a quarter into the Chinese renminbi, and three quarters into the currencies of smaller countries that have played a more limited role as reserve currencies. A characterization of the evolution of the international reserve system in the last 20 years is thus as ongoing movement away from the dollar, a recent if still modest rise in the role of the renminbi, and changes in market liquidity, relative returns and reserve management enhancing the attractions of nontraditional reserve currencies. These observations provide hints of how the international system may evolve going forward.